Sound-letter association and sound blending in preschool children's early reading - Mohamad, Muhaida Akmal; Rafik Galea, Shameem (Malaysian Association of Modern Languages, 2014)
Reading instruction in English to preschool children has been a central issue among reading instructors for decades. It has always centred on whether to begin teaching the children using the lower level or the higher level skills. This paper addresses the issue of teaching preschool children the sound-letter association and sound blending at an early stage when reading in English. Specifically, it focuses on the intervention of sound-letter association in order to demonstrate that learning the sound-letter association first will help preschool children to blend the sounds and eventually to be able to read fluently. We discuss the approaches used and provide evidence based on the pre and post- test results. Our findings indicate that the sound-letter association and sound blending as skills must be acquired by preschool children before they begin to learn reading as it scaffolds their ability to see how sounds and alphabets are related and to read words. We argue that introducing to preschool children sound-letter association and sound blending before moving them into real reading will make them better readers.